Terobosan Hukum Dalam Rahasia Bank - Pelupessy, Berd Elkiopas (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the laws and regulations on bank secrecy, the chronology of the laws and regulations on bank secrecy and the requirements and procedures for issuing written orders or permission to disclose bank secrecy. The research method used is normative and empirical juridical by reviewing and examining the applicable laws and regulations related to legal breakthroughs in bank secrecy and the reality that occurs in the field. The results of the study revealed that empirical reality proves that on the one hand the interests of the community require that the obligation to bank secrecy be upheld by banks, but on the other hand, the interests of the community should not be sidelined for certain matters if the obligation to bank secrecy is carried out firmly. For this purpose, the community wants that for certain matters the obligation to bank secrecy should be excluded. Violation of bank secrecy can result in criminal or civil sanctions for the violators. Customers who feel disadvantaged have the right to claim compensation from the bank that leaks their financial situation or matters concerning customers through the process of suing (litigation) in civil court.